Corrections to “Federated Learning Approach for Breast Cancer Detection Based on DCNN” - Hussain Alsalman; Mabrook S. Al-Rakhami; Taha Alfakih; Mohammad Mehedi Hassan (IEEE Access)
Presents corrections to the paper, (Corrections to “Federated Learning Approach for Breast Cancer Detection Based on DCNN”).